Implikasi Kinerja Keuangan terhadap Tingkat Bagi Hasil Deposito Mudharabah dengan Profitabilitas sebagai Variabel Mediator: Studi pada Bank Umum Syariah - Desi Siti Mariam; Djoni Djatnika; Banter Laksana; Lina Nur Ardila (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to determine the direct and indirect effects of financial performance on Islamic Commercial Banks such as NPF, FDR and BOPO to the level of profit sharing on mudharabah deposits through ROA as a mediator variable in Islamic Commercial Banks for the 2015-2020 period. The data analysis used are Path Analysis and Sobel Test. The research findings indicated that the direct influence of NPF, BOPO, ROA have a positive effect on the rate of profit sharing on mudharabah deposits, FDR had no effect on the rate of profit sharing on mudharabah deposits, NPF had a positive effect on ROA, FDR had no effect on ROA, and BOPO had a negative effect on ROA whilst the indirect effect showed that ROA can mediate NPF and BOPO on the rate of profit sharing on mudharabah deposits, and ROA cannot mediate FDR on the rate of profit sharing on mudharabah deposits